RETRACTED: The information system for the selection of a study direction and skills development in the field of information security - Aidinyan Andrey; Tsvetkova Olga (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001